n-normal weighted composition operator and n-unitary weighted composition operator on Hardy space H2 - H.Abood, Eiman; Hussein Mohammed, Alaa (Al-Qadisiyah Journal of Pure Science, 2018)
In this paper we characterize the n-normal weighted composition operator and n-unitary weighted composition operator on Hardy space H2